Combatting debt bias in South African firms: The case for an allowance for corporate equity - Seppo Kari; Londiwe Khoza; Nangamso Manjezi; Kyle McNabb (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
The problem of debt bias can be tackled through either disincentivizing the use of debt financing or incentivizing the use of equity financing. Considering the South African context - in which many firms are highly leveraged and the marginal effective tax rates for using debt financing are significantly lower than those for equity financing - this study explores the case for introducing an allowance for corporate equity. We show that while such a reform would significantly neutralize the incentives to invest across debt and equity financing, our static simulations - using the NT-SARS CIT-IRP5 panel - show that it would entail a significant revenue loss to the fiscus.
Keywords: H21; H25; H32; O23; 330; debt bias; investment incentives; corporate tax; tax revenue; South Africa